Emergency surgery in octogenarians: Outcomes and factors affecting mortality in the general hospital setting. Issue 8 (13th June 2018) - Bolger, Jarlath C; Zaidi, Akif; Fuentes‐Bonachera, Adrian; Kelly, Michael E; Abbas, Aqeel; Rogers, Ailin; McCormack, Tom; Waldron, Brian; Murray, Kevin P
Abstract : Aim: The Western world has an expanding older population, who are living longer with increasing numbers of comorbidities. In addition, expectations of patients and relatives are increasing. As a general hospital operating in a rural setting, our University Hospital Kerry, Tralee, Ireland, deals with a significant number of emergency presentations to the acute surgical service. The aim of the present study was to examine outcomes for patients in the extremes of age who present requiring emergency surgical procedures. Methods: A retrospective review of theater and admission logs was carried out to identify all emergency surgeries from January 2008 to December 2015. All patients aged >80 years at the time of surgery were identified. Details of surgery were recorded, in addition to biochemical and hematological data, use of intensive care unit, length of stay and mortality. Results: In total, 128 octogenarians underwent an emergency surgery. The average patient age was 84.3 years (range 80–94 years). The commonest procedures were laparotomy (65%, n = 84), repair of strangulated/incarcerated hernia (18%, n = 23) and laparoscopic procedures (16%, n = 21). The 30‐day all‐cause mortality was 22.6%. On multivariate analysis, American Society of Anesthesia status and intensive care unit utilization predicted mortality ( P = 0.04 and 0.05, respectively). A total of 82 patients required intensive care unit admission, with an average length of stay of 4.8 days, using 484 bed days in total. Conclusions: Emergency surgery in octogenarians is a significant part of the workload of general surgeons. Poor baseline status is associated with an increased risk of mortality. Emergency surgery in older adults only utilizes a fraction of available intensive care unit resources.Geriatr Gerontol Int 2018; 18: 1211–1214 .